Les broyeurs en pierre en forme de doigt dans le sud-est de la Gaule romaine - Yves Manniez; Vincent Lauras (Gallia)
Among the small stone objects classified as ancient instrumentum, we sometimes find pestles that have the particularity of representing a bent human finger, generally the thumb and, more rarely, a shod foot, sometimes extended to include a leg. This type of material good is uncommon in Gaul, whereas it appears to be better represented in Greece and in Italy. In addition to the relative paucity of examples, these objects are also often overlooked due to their generally poor state of preservation. They are almost always fragmented and therefore more difficult to accurately identify as pestles. Indeed, such items have been erroneously identified as fragments of statuary. Our corpus is comprised of 51 examples, available for study in either museums or archaeological repositories in the south-eastern quarter of France. As the creation of a typology did not seem relevant, the catalogue of forms was completed with the addition of 28 of the best-preserved examples of the 39 pestles in the Antiquarium of Pompeii. In the first part of our study, and following a review of the history of research carried out by our predecessors on this type of object, we examined and discussed the geographical origin of finger-shaped pestles and their evolution towards stone models. The latter were very popular in the Aegean world and subsequently spread throughout the Roman Empire, until at least the 3rd c. AD. Finally, the various names by which these objects are designated or described in French archaeological literature are presented. In the second part of our study, we used the information relating to the pestles in our catalogue, at times referring to objects discovered outside our area of study. Firstly, we examined the different contexts in which these artefacts were found. As a general rule, they are associated with a stone mortar, as evidenced by a series of terracotta figurines and some bas-reliefs. Such assemblages are often found in the destruction levels of settlements or medical dispensaries, as well as in burials or among the remains of shipwrecks. Following this, we performed a typological analysis of the pestles and defined four groups of instruments that were distinguishable from one another by the presence or absence of a few defining features (depiction of the nail, details of the knuckle features). We also revealed the existence of a foot or leg variant. We then discussed the different pestle models, which vary in height from 50 to 230 mm, and highlighted the rare cases of inscription. Finally, we discussed the various known uses for finger-shaped pestles, attested to by archaeological study or ancient texts, and which include: culinary preparations, the manufacture of cosmetics and pharmaceutical products, as well as the preparation of pigments aimed at habitat decor. Ultimately, this study allowed us to evoke the ancient origin of finger-shaped stone pestles, as well as to discover that this form was inspired by clay objects already attested to in Mesopotamia in the 6th and 5th millennia BC. It was also an opportunity to demonstrate the wide distribution of this unique object throughout the Greco-Roman world between the 5th c. BC and the 3rd c. AD. The diversity of shapes and models that exist for this category of object may sometimes be explained by their intended use, particularly in the case of very small pestles. This multiplicity of form, however, is also likely indicative of the large number of craftsmen responsible for the fabrication of these objects, as well as of the customization and adaptation of certain models to specific users. Finally, these realities make it both difficult and impractical to establish a fixed typology for these finger-shaped pestles.